Four low-carbon futures for a Swedish society beyond GDP growth. (1st November 2019) - Fauré, Eléonore; Finnveden, Göran; Gunnarsson-Östling, Ulrika
Abstract: This paper describes how different backcasting scenarios for developments beyond traditional GDP growth 2050, in Sweden may fulfil a climate goal corresponding to keeping global warming to a maximum 1.5 °C with 50% likelihood. This corresponds to a 92% decrease of greenhouse gas emissions from Swedish consumption from today's level. The four scenarios illustrate different strategies: 1) collaborative economy, 2) local self-sufficiency, 3) automation for quality of life and 4) circular economy in the welfare state. The aim is to further hone and quantify the scenario narratives with a focus on greenhouse gas emissions occurring as a result of Swedish consumption, both private and public. The results show that the climate target can be met in all scenarios but this requires radical sector-specific as well as general changes, including decarbonisation, technology development, increased efficiencies, innovative practices and reduced demand. The mix of these strategies varies for different sectors and different scenarios, but all are needed to reach the climate goals. As we assume that Sweden is fossil-free 2050, particular areas of attention are diets, travel, emission intensities in other countries and the level of imports. Potential implications for other environmental goals, land use and biodiversity as well as the potential magnitude of negative emissions technologies, although uncertain and limited, that could offset some additional greenhouse gas emissions are discussed. Highlights: Four backcasting scenarios for Sweden can meet the 1, 5 °C. climate target by 2050 (83). Radical changes are needed in terms of consumption patterns and reduced demand (80). Areas of attention are diets, transports, imports and global emission intensities (83).